The neglected goat : a new method to assess the role of the goat in the English Middle Ages - Salvagno, Lenny, (Access archaeology., 2020)
Based on a combination of morphological and biometrical analyses, this book provides a new, objective and transparent methodology to distinguish between sheep and goat post cranial bones in the archaeological record. Additionally, on the basis of the newly proposed approach, it reassesses the role of the goat in medieval England.